Food Fight! - Shields, Carol Diggory; Gay-Kassel, Doreen (Brooklyn, N.Y. : Handprint Books, 2002)
Late one night, the salad greens declare "Lettuce have a party!" and food emerges from cabinets and cupboards to join in, until the tuna fish band tells garlic it stinks and things start to go bad.
Keywords: Food -- Fiction; Parties -- Fiction; Fighting (Psychology) -- Fiction; Stories in rhyme